2016
DOI: 10.1155/2016/2614742
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Ginseng and Its Constituents in the Treatment of Central Nervous System Disorders

Abstract: Ginseng, a perennial plant belonging to the Panax genus of the Araliaceae family, has been used in China, Korea, and Japan as a traditional herbal medicine for thousands of years. Ginseng is recorded to have exhibited a wide variety of beneficial pharmacological effects and has become a popular and worldwide known health supplement and drug. The protective effects of ginseng on central nervous system are discussed in this review. Ginseng species and ginsenosides and their intestinal metabolism and bioavailabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 83 publications
0
33
0
Order By: Relevance
“…It could also improve scores on the National Institutes of Health Stroke Scale with similar mortality and adverse event rates when compared with placebo (Liu et al, 2009;Liu et al, 2012). Ginsenoside-Rb1 (G-Rb1) (the chemical structure is shown in Figure 1) is regarded as the major active ingredient (Lee et al, 2015), which has been proven to cause a wide range of biological activities, especially in regards to its neuroprotective role, probably through anti-inflammatory, anti-oxidative, antiapoptosis, anti-stress and anti-depressive effects in vivo and in vitro (Kim, 2012;Kim et al, 2013;Ong et al, 2015;Rokot et al, 2016;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It could also improve scores on the National Institutes of Health Stroke Scale with similar mortality and adverse event rates when compared with placebo (Liu et al, 2009;Liu et al, 2012). Ginsenoside-Rb1 (G-Rb1) (the chemical structure is shown in Figure 1) is regarded as the major active ingredient (Lee et al, 2015), which has been proven to cause a wide range of biological activities, especially in regards to its neuroprotective role, probably through anti-inflammatory, anti-oxidative, antiapoptosis, anti-stress and anti-depressive effects in vivo and in vitro (Kim, 2012;Kim et al, 2013;Ong et al, 2015;Rokot et al, 2016;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng is a perennial plant belonging to the genus Panax and family Aralliaceae [ 1 ]. The word Panax means “all-healing” in Greek based on a view that ginseng is influential in healing all kinds of disease [ 2 ]. Among the different species of ginseng, the most commonly investigated species are Panax ginseng (frequently called as just ginseng or Korean ginseng), P. quinquefolius (also known as American ginseng) and P. notoginseng (also known as Chinese ginseng or Sanchi) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng roots, stems and leaves have been used in traditional herbal medicine for over 2000 years [ 4 ]. Ginseng and its active components have exhibited a wide range of characteristics, including antioxidant, antiaging, antifatigue, adaptogenic, restorative, vasodilatory, anti-inflammatory, immunomodulatory, anticancer and antidiabetic [ 2 , 4 ]. In addition, in models of neurological disorders, the active components of ginseng showed anti-depressive, antistress, antiepileptic and antipsychotic activities [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence has suggested that it can improve neurotransmission in the brain as an important pharmacological effect of PG ( 16 , 17 ). Ginseng and its constituents are known to have beneficial effects on cognitive performance, memory, and neurodegenerative disease ( 18 ). A number of previous studies have focused on the effects of ginseng on central nervous system diseases such as Alzheimer's disease, Parkinson's disease and depression ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%